OVERSIGHT OF THE JUDICIAL AGENCY BY THE JUDICIAL COMMISSION - Surya Ananda (NOMOI Law Review, 2021)
The 1945 Constitution of the Republic of Indonesiaregulates theexistence of the Judicial Commission,the Judicial Commissionhas the authority regulated in the 1945 Constitution Article 24B paragraph (1) which states that the Judicial Commission has the authority to propose the appointment of supreme justices and has other powers in order to protect and upholding the honor, dignity and behavior of judges.The researchuses normative legal researchbyusing akind of normative juridical approach. Based on the results of this study it is understood that the legal arrangements regarding the authority of the judicial commission in the perspective of enforcing the code of ethics in the judiciary have not fully provided enforcement of violations of the code of ethics and guidelines for judges' behavior to the Judicial Commission.Because the decision issued by the Judicial Commission itself is still a recommendation, which means that it must be discussed jointly by the Supreme Court in determining and imposing sanctions on judges who are proven to have violated the code of ethics and code of conduct of judges.Keywords:Supervision, Judges, Judiciary, and Judicial Commission